Hubungan Gaya Hidup Terhadap Kejadian GERD (Gastroesophageal Reflux Disease) di RSUD Koja Jakarta Utara - Suzanna Ndraha; Grace Abigaelni Harefa; Bhannu Khumar (Jurnal MedScientiae, 2023)
The risk factors of GERD include medication, food, hormone, structural and body mass index (BMI) and other lifestyle factors. Aim of this study is to determine the correlation between lifestyle (smoking, BMI, coffee consumption, spicy food consumption, alcohol, sleeping without pillow, eating late at night) and GERD in Koja Regional Hospital. This study using logistic regression analysis with accessible population was all patients visited Internal Medicine Clinic in Koja Regional Hospital. Data were collected in Augustus 2019-September 2019, using questionnaires and interviews. There were 102 subjects, 68% female, 47% aged > 50 years 47%. Only 27% smoking, 42% BMI above normal, 8% drink alcohol, 26% sleeping without pillow, 38% eating late at night, 45% coffee consumption, 84% consumed spicy foods. Logistic regression analysis found the correlation between smoking, BMI, coffee consumption, spicy food consumption, alcohol, sleeping without pillow, eating late at night altogether and GERD in Koja Regional Hospital. But using partial logistic regression analysis, only spicy food consumption had significant correlation with GERD in Koja Regional Hospital. Spicy food consumption had risk to have GERD 14,671 times than who did not.